Breathless - Niven, Jennifer (Alfred A. Knopf, 2020)
From Jennifer Niven, the #1 New York Times bestselling author of All the Bright Places, comes an unforgettable new novel about a sensitive girl ready to live her bravest life--sex, heartbreak, family dramas, and all. Before: With graduation on the horizon, budding writer Claudine Henry is focused on three things: college in the fall, become a famous author, and the ever-elusive possibility of sex. She doesn't even need to be in love--sex is all she's looking for. Then her dad drops a bombshell: he and Claude's mom are splitting up. Suddenly, Claude's entire world feels like a lie, and the ground under her feet anything but stable. After: Claude's mom whisks them both away to a remote, mosquito-infested island off the coast of Georgia, a place where the two of them can start the painful process of mending their broken hearts. It's the last place Claude can imagine finding her footing, but then Jeremiah Crew happens. Miah is a local trail guide with a passion for photography, and a past he doesn't like to talk about. He's brash, enigmatic, and even more infuriatingly, he's the only one who seems to see Claude for who she wants to be. So when Claude decides to sleep with Miah, she tells herself it's just sex--exactly what she has planned. There isn't enough time to fall in love, especially if it means putting her already broken heart at risk. Compulsively readable and impossible to forget, Jennifer Niven's luminous new novel is an insightful portrait of a young woman determined to write her own next chapter--sex, resilience, mosquito bites, and all.